PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBENTUK RANGKUMAN KOSAKATA (RAKOS) UNTUK MENINGKATKAN PENGUASAAN KOSAKATA ILMIAH SISWA DI MTS MIFTAHUL JANNAH TANGERANG - Berliana Dewi Adinda, - (2022)
Vocabulary mastery is one of the difficulties experienced by students in the learning process, especially the scientific vocabulary. Although the implementation of a scientific vocabulary often occurs in students daily lives, the reality is that there are still many students who don't understand the meaning of the vocabulary because the language used is very rarely heard. This research discusses how the process developing of digital comics learning media in a scientific vocabulary summaries (Rakos) to enhance students scientific vocabulary at the middle school level. The purpose of this research is to describe how the process of developing digital comic learning media of vocabulary summaries (Rakos), how the experts assessment when validating media and materials, and how the user assessment when using the media. The method used to conduct this research is the ADDIE Design and Development model developed by Dick & Carry which consists of five stages of analyze, design, development, implementation, and evaluation. The population of this study is students at MTs Miftahul Jannah with a sample of 30 students from class VII based on clustering sampling. The results obtained from this study are learning media product of digital comics that contain a summary of scientific vocabulary on biotic component material that can be accessed online. In addition, based on the assessment from experts and user, the digital comics learning media that summarizes the vocabulary (Rakos) is appropriate to be used in the learning process to help students enhance the scientific vocabulary and learning motivation.